Are non-risk based capital requirements for insurance companies binding? - de Haan, Leo; Kakes, Jan (Journal of Banking & Finance, 2010)
We investigate whether insurers base their solvency margins on risk factors even when operating under a supervisory regime where minimum solvency requirements do not fully take such risk factors into account. To do this, we use a dataset of about 350 Dutch insurers from all major lines of business during the pre-Solvency II period 1995–2005. We find that the levels of insurers’ actual solvency margins are related to their risk characteristics and not to regulatory solvency requirements. Consequently, the vast majority of insurers hold much more capital than required, i.e. non-risk based capital requirements generally are not binding. Requirements are found to affect solvency adjustment behaviour, though. More specifically, below-target capital ratios are raised most rapidly by those insurers whose targets are relatively close to the regulatory minimum. One implication from our results is that, because insurers already follow a risk-based approach, the transition to the new European regulatory framework, Solvency II, is likely to be smooth.